2018
DOI: 10.21873/anticanres.12998
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients in the Emergency Department: A “Nightmare” that Might Become a Virtuous Clinical Pathway

Abstract: Background/Aim: Emergency departments (EDs) often face overcrowding issues while simultaneously confronting with the increasing clinical needs of patients, such as cancer patients, with both acute and chronic illnesses. In order to guarantee a prompt and specialized treatment of ED-attending cancer patients and reduce inappropriate inpatient admissions, a dedicated ED cancer pathway (EDCP) consisting of EDbound Medical Oncology (MO) resident doctor and direct admission for candidate patients exclusively to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Research demonstrates that cancer-specific pathways in general within an ED triage system can improve outcomes in terms of inpatient admission, decreased ED visits, and decreased overall mortality. [27][28][29] Given the variable outcomes among different cancer subtypes our study underscores importance of considering cancer type in the risk stratification process of this uniquely vulnerable patient population.…”
Section: Discussionmentioning
confidence: 89%
“…Research demonstrates that cancer-specific pathways in general within an ED triage system can improve outcomes in terms of inpatient admission, decreased ED visits, and decreased overall mortality. [27][28][29] Given the variable outcomes among different cancer subtypes our study underscores importance of considering cancer type in the risk stratification process of this uniquely vulnerable patient population.…”
Section: Discussionmentioning
confidence: 89%
“…Universally, pain remains a dominant reason for emergency service usage among cancer patients [ 12 ], as well as a significant predictor for hospital readmission and mortality [ 13 ]. The management of cancer patients admitted to emergency services in dedicated oncology pathways has been shown to improve health care [ 14 ]. Moreover, a large population-based projection study showed that by 2060, cancer patients will die of unnecessary health related suffering unless an expansion of palliative care is integrated into cancer programs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, emergency physicians should be trained with a specific curriculum during their university course work focusing on acute care of cancer patients [16]. Some authors evaluated the benefit of embedding an oncologist in the ED with discordant results on patients' admission rates [17,18]. We think that acute complications of cancer patients need to be dealt with an emergency physicians in the same way as any other acute complications of another chronic disease.…”
Section: Discussionmentioning
confidence: 99%